Effect of Peer-Led and Professional-Led Oral Health Education on KAP of Child Bearing Age Females - A Randomized Controlled Trial - Faiza Awais, Muhammad Mohsin Kamal, Sara Ijaz, Muhammad Behzad Salahuddin, Ehsan Rathore, Waleed Javaid Toosy (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To compare the effect of peer led and professional led oral health education on knowledge, attitude and practicesof child bearing age females. Methods: The design for this study was a randomized controlled trial in which changes in knowledge, attitude and practices were compared after providing peer and professional-led education.480 females of child bearing age in BHU Raiwind and 500 in Araiyaan were randomly selected for the study. Brushing frequency, brushing timing and fluoride prevention outcomes were compared statistically. Results:The results indicated that brushing twice a day after intervention in peer group increased to 24% from 16% (baseline) but again dropped to almost 15% at follow-up. Brushing twice a day in professional-led group was 17% at baseline which increased to 36% after intervention; though it reduced to 31% at follow-up.It was found out in peer-led group that at baseline 24.6% considered fluoride helpful in preventing oral diseases, this increased twofold in intervention visit but again dropped at follow up (still more than that at baseline). While in professional group 24.1% (same as in peer-led) thought fluoride helpful in preventing dental diseases but here in intervention visit this increased more than three times (82%) and dropped to 40% which is still more than baseline data. Conclusion:Professional led Health education significantly played an important role in adopting healthy oral hygiene habits among females of child bearing age. Health Education provided by the peers also improved the oral health conditions. Keywords: Health Education, Oral Health Education, Oral health Awareness, Professional led health Education.